2009
DOI: 10.1080/13685530902777425
|View full text |Cite
|
Sign up to set email alerts
|

Association between severity of lower urinary tract symptoms, erectile dysfunction and metabolic syndrome

Abstract: Obesity, high plasma level of FBG and hypertension constitute risk factors for the development of severe LUTS. Metabolic syndrome may play a key role in the pathogenesis in both ED and LUTS. Presence of ED is the most predictor of severe LUTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 29 publications
1
57
0
1
Order By: Relevance
“…Other measurements of health including obesity, osteoporosis, cardiovascular disease, cognition, and activities of daily living (ADLs) were not statistically different between normal testosterone and hypogonadal groups. Results from Demir et al supported these findings, and also showed ED was the strongest predictor of severe LUTS in a series of 190 men [12]. Prevalence of metabolic syndrome was also statistically higher in men with severe LUTS (p=0.009).…”
Section: Etiology and Effects Of Hypogonadism In Elderly Mensupporting
confidence: 76%
“…Other measurements of health including obesity, osteoporosis, cardiovascular disease, cognition, and activities of daily living (ADLs) were not statistically different between normal testosterone and hypogonadal groups. Results from Demir et al supported these findings, and also showed ED was the strongest predictor of severe LUTS in a series of 190 men [12]. Prevalence of metabolic syndrome was also statistically higher in men with severe LUTS (p=0.009).…”
Section: Etiology and Effects Of Hypogonadism In Elderly Mensupporting
confidence: 76%
“…The linkage between MetS and erectile dysfunction (ED) has been highlighted by many studies. [1][2][3] MetS and ED are suggested to share common pathophysiological factors including insulin-resistance, endothelial dysfunction and systemic inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%
“…IPSS scores increase in parallel with decreases in IIEF scores. On the contrary, Demir et al [19] could not find a significant association between LUTS, hypertension, diabetes mellitus, and abdominal obesity. In their study signifcantly higher frequency of lower urinary tract symptoms were found in cases with hypertriglyceridemia (28.8% vs. 53.8%).…”
Section: Discussionmentioning
confidence: 86%
“…In separate analyses of each risk factors, frequency of ED was found to be increased in the presence of mild (1.9-fold), moderate (3.7-fold), and severe (7.6-fold) ED. [18] In a study by Demir et al [19] a significant degree of concomitancy was detected between LUTS, and ED. They found 2.4-fold higher incidence of ED in patients with LUTS.…”
Section: Discussionmentioning
confidence: 99%